Trudności i korzyści aplikacji zintegrowanego systemu zarządzania jakością, środowiskiem i BHP - wyniki badań - Sus-Januchowska, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the present paper an integration of three management systems: quality (according to ISO 9001:2000), environmental (according to ISO 14001) and work security (according to PN-N 18001) are shown. This article's goal is to propose advantages and disadvantages of the application of those systems. It should be noted that this model is the most profitable one for an organization, because it makes structures clearer, improves the mechanism for continual improvement and makes a complex approach to all of problems in an organization possible. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 245-252